Pragmatic Emphasis as A Scaffolding Tool: A Relevance Theoretic Analysis of Instructional Communication - Charles Bryan D. Beloy (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study investigates the use of micro-level pragmatic emphasis strategies of teachers as online cognitive scaffolding devices to negotiate working memory limitations and to mark the instructional salience of dense lectures. Based on Sperber and Wilson's Relevance Theory, it analyzes a corpus of spontaneous discourse from a Senior High School Creative Writing lesson to classify spoken emphasis markers evaluative adjectives, assertive adverbs, intensifiers, and directives into functional sub-types. The findings indicate that these markers function as real-time cognitive regulators, with forms tailored to the level of processing demand at hand: affirmative descriptors provide low-effort validation and consolidate abstract writing standards into easily memorable anchors; high-certainty adverbs eliminate ambiguity in subjective concepts; and pre-task intensifiers act as attentional triggers prior to complex task execution. The choice of marker aligns with the pedagogical phase in which it is employed, while localized Taglish code-switching combined with structured repetition reduces both processing effort and social distance. The research ultimately shows that conscious vocal emphasis in the teacher's speech is a crucial pedagogical device for handling cognitive load and optimizing student processing in the moment.